UMKM Sekitar Pondok Pesantren Temboro dalam Meningkatkan Pendapatannya - Bintari, Selfia; Cahyono, Hendry (Universitas Negeri Surabaya, 2023)
MSMEs will grow in places that attract people to engage in economic activities. One of the high activities carried out by students in one of the Islamic boarding schools in Magetan Regency is Temboro village. Therefore, the aim of this research is to examine the extent to which business opening hours, promotional strategies implemented, funding assistance and raw material costs have an influence on increasing the income of MSMEs. The method used in this research is a quantitative descriptive method using regression. The results of the analysis carried out show that high business opening hours can influence the income of MSMEs around the Temboro Islamic boarding school. MSMEs that carry out good promotional strategies are also able to increase income. Meanwhile, funding assistance provided by relevant stakeholders has not been able to influence the income of business actors in Temboro Village, this is because the assistance provided to MSMEs is less than optimal. However, the cost of raw materials which increases over time as inflation increases can have a negative effect on the income of MSMEs.